Visiones cinematográficas del turismo costero: el punto de vista de los excluidos (El verdugo -1963-, Justino un asesino de la tercera edad -1994-, Barrio -1999-) - Nancy Berthier (Cahiers de Civilisation Espagnole Contemporaine)
The careful examination of three Spanish films from a sharp focus on the representation of what means coastal tourism for those who can't enjoy it, reveals beyond its undoubted differences, the permanence of a reflection on the national cinema, a reflection on exclusion. In Western consumer societies, where tourism becomes economically possible only after solving the priority expenses of daily living (food, shelter, clothing), it appears to be what causes most people sociocultural difference in their lifestyle.